NOVO COMPOSTO DE COORDENAÇÃO CONTENDO ÍONS FEIII E LIGANTE ESTABILIZADOR DE ESPÉCIES METALO-FENOXIL - Sotto, Jaqueline; Macedo, Michele; Biscoli, Leandro; Faganello, Natali; Favero, Vanessa; Anjos, Ademir (ANAIS DO ENIC, 2018)
-